Intervenção fonoaudiológica com professores: análise de uma proposta realizada na modalidade de Educação a Distância - Pompeu, Ana Terra Santos (2016)
Among the voice professionals, teachers have been studied a lot, however just a few initiatives are aimed to assess the speech therapy with this audience. A voice therapy presential action is complex when it comes to large numbers of teachers, large territorial extension and also for complex routine work of teachers. This is the case of São Paulo Municipal Education Network teachers. Thus, distance learning (DL) seems to be a method that brings benefits as it offers flexibility of time, savings in travel to the site of the workshop, management regarding the pace of learning and opportunity to study from new methodologies and technologies. Objective: to analyze a proposal for voice therapy intervetion performed remotely with teachers of São Paulo Municipal Education Network, focusing on raising awareness of the participants on the issues of vocal welfare. Method: 110 teachers signed up to attend a voice therapy intervention in distance learning mode after the call made through Diário Oficial do Município, and of those, 68 were able to complete the intervention, these being the subject of this research. Participants were submitted to an 40 hours intervention, 36 divided into eight modules, eight forums, eight evaluations and 16 distance chat rooms, besides four hours, in two face meetings. The workshop material was inserted into the Moodle platform of São Paulo City Hall. A pilot initiative was carried out earlier with 100 teachers, and intervention applied in this study took into account the changes made from that experience. Data collection consisted of: records collected during the workshop within the forums and chat rooms corresponding to the eight modules; a research diary used in the occasion of the fortnightly meetings of the group manager and tutors as well as the two regular classes; and two questionnaires given to participants at the end of the workshop, one used by the team responsible for the platform, another prepared especially for this research. All material of the participants were subjected to thematic analysis as it prioritized three areas: structure, process (subdivided into learned that ... I realized that ... I put into practice ...) and the result. Results: Among the 58 comments (21.3%) were related to having learned that the teacher is a voice professional; 63 (22.1%) for not having realized before how they breath and now recognize that breathing is fundamental to the voice quality; and 61 (45.5%) have put into practice the use of verbal and non-verbal resources also learned in the workshop. In the overall assessment of the workshop held by the platform, 49 (98%) said were approached topics of their interest in the workshop and all the participants believe that this learning was important to their professional practice. The tutor-student relationship, 47 (98%) indicated that the tutor encouraged him to participate, and all of them said it had obtained knowledge of voice that they did not have and which sought to put them into practice, noting that the presented content has been clarified. Conclusion: The workshop on distance learning modality reached the goals, as constituted at a time of listening to the needs of the teacher and proposed reflection tools so that it could initiate a movement that may be agents of their own health, and that through knowledge, to act for their own benefit and consequently their students